Locally delivered adjuvant biofilm‐penetrating antibiotics rescue impaired endochondral fracture healing caused by MRSA infection. Issue 2 (13th January 2021) - Cahill, Sean V.; Kwon, Hyuk‐Kwon; Back, Jungho; Lee, Inkyu; Lee, Saelim; Alder, Kareme D.; Hao, Zichen; Yu, Kristin E.; Dussik, Christopher M.; Kyriakides, Themis R.; Lee, Francis Y.
Abstract: Infection is a devastating complication following an open fracture. We investigated whether local rifampin‐loaded hydrogel can combat infection and improve healing in a murine model of methicillin‐resistant Staphylococcus aureus (MRSA) osteomyelitis. A transverse fracture was made at the tibia midshaft of C57BL/6J mice aged 10–12 weeks and stabilized with an intramedullary pin. A total of 1 × 10 6 colony‐forming units (CFU) of MRSA was inoculated. A collagen‐based hydrogel containing low‐dose (60 μg) and high‐dose (300 μg) rifampin was applied before closure. Postoperative treatment response was assessed through bacterial CFU counts from tissue and hardware, tibial radiographs and microcomputed tomography (μCT), immunohistochemistry, and histological analyses. All untreated MRSA‐infected fractures progressed to nonunion by 28 days with profuse MRSA colonization. Infected fractures demonstrated decreased soft callus formation on safranin O stain compared to controls. Areas of dense interleukin‐1β stain were associated with poor callus formation. High‐dose rifampin hydrogels reduced the average MRSA load in tissue ( p  < 0.0001) and implants ( p  = 0.041). Low‐dose rifampin hydrogels reduced tissue bacterial load by 50% ( p  = 0.021). Among sterile models, 88% achieved union compared to 0% of those infected. Mean radiographic union scale in tibia scores improved from 6 to 8.7 with high‐dose rifampin hydrogel ( p  = 0.024) and to 10 with combination local/systemic rifampin therapy ( p  < 0.0001). μCT demonstrated reactive bone formation in MRSA infection. Histology demonstrated restored fracture healing with bacterial elimination. Rifampin‐loaded hydrogels suppressed osteomyelitis, prevented implant colonization, and improved healing. Systemic rifampin was more effective at eliminating infection and improving fracture healing. Further investigation into rifampin‐loaded hydrogels is required to correlate these findings with clinical efficacy.